Factors Associated with Medication Administration of Home-Based Patient by Caregiver - Utthiya, Pinyo; Sereewichayasawad, Nitchatima; Wonganu, Aree; Srisawatchim, Siriporn; Wongthong, Suphaluck; Kadbua, Sivaporn; Arunsinprasert, Chotnapa (Journal of The Royal Thai Army Nurses, 2022)
This study is a cross-sectional study that aims to study factors relating to drug administration of home patients by using a sample group of patients and caregivers referred to the home health care unit. 70 samples are selected by purposive sampling. Research instruments used include a questionnaire for general information of patients and caregivers, an evaluation form for ability to do daily routines and a monitoring form for drug administration error at home. The inter rater reliability is found to be 0.68 – 0.79 and 1.00, respectively. Data is analyzed using descriptive statistics and Chi-Square (χ2) test statistics From the analysis of the patient factor relating to home drug administration based on 6Rs, it is found that gender and the amount of drug are significantly correlated with the right dose medication at the statistical level of .05 (χ2 = .020 and χ2 = .02, respectively). Comorbidities and the amount of drug are significantly correlated with the right patient medication at the statistical level of .05 (χ2 = .037 and χ2 = .042, respectively). As for the caregiver factor, it is found that the age of caregiver is significantly correlated with the right time medication at the statistical level of .05 (χ2 = .021). This study finds that a dependent elderly patient with medication or a higher number of comorbidities need a main caregiver to help with home drug administration in order to reduce the drug administration error.